Strategic Leadership in the Department of Labour in Gauteng - Maseko, Siyabonga Joseph (My University, 2013)
The Labour Market Information and Statistics business unit of the Gauteng provincial office of the Department of Labour experiences challenges due to the lack of strategic leadership. This research was aimed at exploring these challenges in the execution of the Gauteng Department of Labour’s provincial office merger with regard to the implementation of the Labour Market Information and Statistics business unit. Using a qualitative approach and qualitative interviews, the factors that lead to the lack of strategic leadership in the Labour Market Information and Statistics business unit were investigated. The findings reveal that the merger of the former North and South Labour Market Information and Statistics business unit of the Gauteng Province affected the functioning of the business unit. This was found to be as a result of the lack of an updated strategy of the business unit. These results in managers in the unit not to being able to play their strategic leadership role, as planning, communication and strategic understanding affected the implementation of the unit’s strategy
MM (P&DM) thesis
Keywords: Leadership; Leadership in government